2018
DOI: 10.1159/000494476
|View full text |Cite
|
Sign up to set email alerts
|

Pinostilbene Hydrate Suppresses Human Oral Cancer Cell Metastasis by Downregulation of Matrix Metalloproteinase-2 Through the Mitogen-Activated Protein Kinase Signaling Pathway

Abstract: Background/Aims: Cancer is the most common cause of death worldwide with approximately one third of people being diagnosed with cancer in their lifetime. Pinostilbene hydrate (PSH) A methylated derivative of resveratrol Has been reported to possess antioxidative Cardioprotective and anticancer properties. However the antimetastatic effect of pinostilbene in oral squamous cell carcinoma (OSCC) remains unknown. Methods: In this study We investigated the effect of PSH on antimetastatic activity and the relevant s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 35 publications
0
21
1
Order By: Relevance
“…In addition, the activation ratio of MMP‐2 significantly increased in patients with lymph node metastasis compared with patients without lymph node metastasis . The inhibition of MMP‐2 protein expression can effectively reduce the migratory ability of oral cancer cells …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, the activation ratio of MMP‐2 significantly increased in patients with lymph node metastasis compared with patients without lymph node metastasis . The inhibition of MMP‐2 protein expression can effectively reduce the migratory ability of oral cancer cells …”
Section: Discussionmentioning
confidence: 97%
“…51 The inhibition of MMP-2 protein expression can effectively reduce the migratory ability of oral cancer cells. 52,53 To elucidate the mechanism of geraniin's suppression of the invasion and migration of oral cancer cells by the downregulation of MMP-2, the signaling pathways that are frequently involved in the tumorigenesis in human cancers were examined. The present study revealed that FAK, Src, and MAPK ERK1/2 were involved in the process ( Figure 5).…”
Section: Traditional Chinese Medicine (Tcm) Originated In Ancient Chinamentioning
confidence: 99%
“…Kasten, East Tennessee State University, Quillen College of Medicine, Johnson City, TN. Culture conditions of both OSCC cell lines were maintained in Dulbecco's Modified Eagle Medium/Ham's F12 Nutrient Mixture (DMEM/F12; Life Technologies, Grand Island, NY, USA) supplemented with 10% fetal bovine serum (FBS) (Gibco, Grand Island, NY, USA) and other essential supplements as previously described [60]. The SG cells were cultured in DMEM medium supplemented with 10% FBS.…”
Section: Cell Lines and Reagentsmentioning
confidence: 99%
“…Another oral cancer cell line, Ca9-22, was obtained from and authenticated by the Japanese Collection of Research Bioresources Cell Bank (JCRB, Shinjuku, Japan). Dulbecco's Modified Eagle Medium (DMEM; Life Technologies, Grand Island, NY) containing nutritional supplements (as described previously) was used to culture the cells (18). The cells were kept inside an incubator, under humidified condition (temp: 37 • C; CO 2 : 5%).…”
Section: Cell Culturementioning
confidence: 99%
“…Trans-well assay was carried out to examine the migratory and invasive properties of FaDu and CA9-22 cells (Greiner Bio-One, North Carolina, USA). The cells were seeded onto transwell inserts (the upper well containing serum-free medium), incubated for 24 h, and allowed to migrate, as defined earlier (18,20). Next, the cells were examined and photographed under a light microscope for the analysis of cellular migration and invasion.…”
Section: Cell Migration and Invasion Assaymentioning
confidence: 99%